2021
DOI: 10.1158/0008-5472.can-21-0732
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing Ceritinib Induces DNA Damage and Enhances PARP Inhibitor Responses in High-Grade Serous Ovarian Carcinoma

Abstract: PARP inhibitors (PARPi) have activity in homologous recombination (HR) repair-deficient, high-grade serous ovarian cancers (HGSOC). However, even responsive tumors develop PARPi resistance, highlighting the need to delay or prevent the appearance of PARPi resistance. Here, we showed that the ALK kinase inhibitor ceritinib synergizes with PARPis by inhibiting complex I of the mitochondrial electron transport chain, which increases production of reactive oxygen species (ROS) and subsequent induction of oxidative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…These mechanisms suggest that ceritinib combined with PARPis may increase its therapeutic efficacy in cancer. The combination of ceritinib and olaparib showed superior cancer inhibition in OC cell lines, and also in the HGSOC PDX model; the results showed that ceritinib monotherapy had no significant effect, but it could increase the therapeutic effect of olaparib in the PDX model ( Kanakkanthara et al, 2022 ), and this result provides the basis for the clinical study on the combination of these two. There is currently no clinical trial to further explore the effect of the combined use of these two drugs on the clinical benefit of patients, which is also the direction of future research.…”
Section: Overcoming Resistance To Parpimentioning
confidence: 81%
“…These mechanisms suggest that ceritinib combined with PARPis may increase its therapeutic efficacy in cancer. The combination of ceritinib and olaparib showed superior cancer inhibition in OC cell lines, and also in the HGSOC PDX model; the results showed that ceritinib monotherapy had no significant effect, but it could increase the therapeutic effect of olaparib in the PDX model ( Kanakkanthara et al, 2022 ), and this result provides the basis for the clinical study on the combination of these two. There is currently no clinical trial to further explore the effect of the combined use of these two drugs on the clinical benefit of patients, which is also the direction of future research.…”
Section: Overcoming Resistance To Parpimentioning
confidence: 81%
“…Thus, novel combination strategies are required to efficiently inhibit the growth and development of platinum-resistant OC cells. Recent studies have also demonstrated that the use of olaparib in combination with other agents exerted complementary mechanisms of cytotoxicity [ 44 46 ]. Our previous study highlighted the synergistic effects of PARPi and ATO in HR-proficient OC cells [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of NADPH deficiency because of IDH2 mutant activity slows down the conversion of oxidized glutathione (GSSG) to reduced glutathione (GSH), which is a major antioxidant against oxidative stress induced by reactive oxygen species (ROS), and this may lead to ROS accumulation and oxidative DNA damage to promote tumor cell growth 23 , 24 . However, the present data showed that overexpression of IDH2 point mutations, except for R172P, reduced ROS levels in 293T cells under normal conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%